2009
DOI: 10.1143/jpsj.78.064702
|View full text |Cite
|
Sign up to set email alerts
|

Rattling-Induced Superconductiviy in the β-Pyrochlore Oxides AOs2O6

Abstract: The superconducting properties of two -pyrochlore oxides, CsOs 2 O 6 and RbOs 2 O 6 , are studied by thermodynamic and transport measurements using high-quality single crystals. It is shown that the character of superconductivity changes systematically from weak coupling for CsOs 2 O 6 to moderately strong coupling for RbOs 2 O 6 , and finally to extremely strong coupling with BCS-type superconductivity for KOs 2 O 6 , with increasing T c . Strong-coupling correction analyses of the superconducting properties … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
131
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(134 citation statements)
references
References 114 publications
(314 reference statements)
2
131
0
Order By: Relevance
“…Single crystals of KOs 2 O 6 were prepared by the flux method starting from a 1.3:1 mixture of KOsO 4 and OsO 2 in a quartz ampoule at 748 K for 24 h. Polycrystalline samples were prepared as reported previously. 1) Resistivity measurements were carried out on a single crystal of 0.3 × 0.1 × 0.1 mm 3 size by the four-probe method at a current of 10 mA.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Single crystals of KOs 2 O 6 were prepared by the flux method starting from a 1.3:1 mixture of KOsO 4 and OsO 2 in a quartz ampoule at 748 K for 24 h. Polycrystalline samples were prepared as reported previously. 1) Resistivity measurements were carried out on a single crystal of 0.3 × 0.1 × 0.1 mm 3 size by the four-probe method at a current of 10 mA.…”
Section: Methodsmentioning
confidence: 99%
“…The β-pyrochlore oxides AOs 2 O 6 have recently been attracting much attention, [1][2][3][4] as they exhibit an unusual atomic vibration in a solid called rattling, 5,6) which is essentially a local, anharmonic vibration of a heavy ion confined in an oversized atomic cage. They crystallize in a cubic crystal structure of space group Fd-3m with all the atoms sitting at special positions, i.e., the A, Os and O atoms at the 8b, 16c and 48f sites, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[38][39][40] not accompanied by any symmetry breaking. 23,24) It has been reported that electric resistivity is in proportion to T 2 for T < T p , while it behaves as / ffiffiffi ffi T p for T > T p . In the peculiar behavior at high temperatures, it has been suggested that anharmonic phonons play important roles.…”
Section: Introductionmentioning
confidence: 99%